Quality of Life and Depressive Symptoms Among Peruvian University Students During the COVID-19 Pandemic - Figueroa-Quiñones, Joel; Cjuno, Julio; Machay-Pak, Daniel; Ipanaqué-Zapata, Miguel (Frontiers in Psychology, 2022)
Objective: To determine the factors associated with quality of life and depressive symptoms in Peruvian university students during the COVID-19 pandemic. Methods: Multicentre study in 1634 students recruited by convenience sampling. The quality of life (QoL) was assessed with the European Quality of Life-5 Dimensions at three levels (EQ-5D-3L) and depressive symptoms with the Patient Health Questionnaire-9 (PHQ-9). To assess factors associated with QoL and depressive symptoms, linear regressions and fitted regressions were used, with robust coefficients of variance information (β). Results: 345 (21.1%) reported problems in performing daily activities, 544 (33.3%) reported pain and discomfort, 772 (47.2%) were moderately/very anxious or depressed. Furthermore, 207 (12.7%) had moderate-severe and severe depressive symptoms. Men reported better QoL than women (β: 3.2; 95% CI: 1.1, 5.4; p = 0.004) and fewer depressive symptoms (β: -0.7; 95% CI: -1.3, -0.2; p = 0.011). Ayacucho´s residents had more depressive symptoms than Ancash´s residents (β: 0.8; 95% CI: 0.1, 1.5; p = 0.022) and Piura´s residents had fewer depressive symptoms than Ancash´s residents (β: - 1.195% CI: - 1.8, -0.3, p = 0.005). Students who left home during quarantine reported more depressive symptoms (β: 0.7, 95% CI: 0.2, 1.2, p = 0.006). Conclusions: Problems performing daily activities, pain and discomfort, as well as mild to severe depressive symptoms were found in more than three-quarters of the sample. Authorities could consider depression care to improve quality of life in regions where high rates of infection occurred during the pandemic.